LEVEL TAXONOMIC STRUCTURE OF OBSERVED LEARNING OUTCOME (SOLO) BASED ON UNDERSTANDING OF STUDENTS' MATHEMATICS CONCEPTS AT MTS AL-ITTIHAAD MA’ARIF NU 1 PURWOKERTO BARAT - Ibrahim Ibrahim (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2022)
The SOLO taxonomy is used to determine the students' conceptual understanding ability when solving mathematical problems based on criteria/levels. Understanding the concept is a learning process that must be achieved by students. This study aims to analyze students' understanding of mathematical concepts based on the SOLO taxonomy on set material at Mts Al-Ittihaad Ma'arif Nu 1 Purwokerto Barat. The research method used in this thesis is descriptive qualitative. The results showed that students' understanding of mathematical concepts based on the SOLO taxonomy on the set material, in the category of low concept understanding students were on the prestructural level SOLO taxonomy indicators. Because students only have little information and do not form a unified concept so that students cannot complete the given task correctly. In the category of medium concept understanding, students are in the SOLO taxonomy indicators at the unistructural level and the multistructural level. At the unistructural level students have been able to use single information and use a solving process to solve problems and form a unified concept. At the multistructural level students can use some information separately, and can make some relationships from some of this information. In the category of high concept understanding, students are at the relational level SOLO taxonomy indicators. At this level students are able to connect some of the existing information and then apply the concept to real problems.